The Pfeiffer book of successful team-building tools : best of the annuals - Biech, Elaine (Pfeiffer essential resources for training and HR professionals., 2008)
Year after year, consultants, trainers, and human resource professionals have come to rely on The Pfeiffer Annuals to provide them with the most current and quality tools on a wide variety of topics. In this book, editor Elaine Biech and contributors to the Annuals have honed in on the important theme of team building to create the first topic-specific book in The Pfeiffer Annuals series. The Pfeiffer Book of Successful Team-Building Tools, 2nd Edition, includes an innovative ten-block model for building a high-performance team and draws on.